PENGARUH PENERAPAN STRATEGI THINK TALK WRITE (TTW) DENGAN BANTUAN LEMBAR KERJA SISWA (LKS) TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Despi Rahma; Endriyeni Endriyeni (Hipotenusa Journal of Research Mathematics Education (HJRME), 2018)
The success of students in learning is not only determined by the level of students' ability in mastering the concepts of the material that has been taught by the teacher, it is also influenced by the learning situation. With a good level of ability, students are easier to absorb and master the material presented. A good situation will allow students to interact with the teacher and with other students, in solving the problems they face. Think talk write strategy can generate desire and interest in learning, generate motivation, stimulate learning activities and even have a psychological effect on students.In this study the method used is a quantitative method. The population in this study were 7th grade students of SMP N 25 B. Lampung, totaling 219 students and 62 students as the research sample. The sampling technique used cluster random sampling technique. The research instrument used a test question in the form of an essay, in the test there were 10 question items. To find out the quality of the instrument, the validity test uses logical validity by means of construction validity and for the reliability test, the result is 0.844, thus it is included in the high category. The results obtained thit = 6.56 For a significant level of 5% obtained tdaf = 2.00 For a significant level of 1% obtained tdaf = 2.66. In accordance with the criteria for rejecting Ho if thit > t(1-1/2) then Ha is accepted. So reject Ho, which means the application of the use of think talk write strategy can improve students' mathematics learning outcomes or Ha is accepted. (1) The application of think talk write strategy can improve students' mathematics learning outcomes. (2) Students' mathematics learning outcomes with the application of think talk write strategies are higher than students' mathematics learning outcomes without using think talk write strategies.